2001
DOI: 10.1021/ja003503d
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Kinetic Isotope Effects on the Haloalkane Dehalogenase Reaction

Abstract: We have found chlorine kinetic isotope effects on the dehalogenation catalyzed by haloalkane dehalogenase from Xanthobacter autotrophicus GJ10 to be 1.0045 +/- 0.0004 for 1,2-dichloroethane and 1.0066 +/- 0.0004 for 1-chlorobutane. The latter isotope effect approaches the intrinsic chlorine kinetic isotope effect for the dehalogenation step. The intrinsic isotope effect has been modeled using semiempirical and DFT theory levels using the ONIOM QM/QM scheme. Our results indicate that the dehalogenation step is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 63 publications
2
53
1
Order By: Relevance
“…An approach to further constrain this variability is to calculate reference values for a specific reaction acting on a specific molecule. This approach is only feasible if the structure of the transition state is sufficiently known, as was shown recently for chlorine isotope effects associated with dehalogenation of chlorinated alkanes by a haloalkane dehalogenase (106). A good agreement between calculated and experimental values was observed.…”
Section: Implications and Future Research Needsmentioning
confidence: 63%
“…An approach to further constrain this variability is to calculate reference values for a specific reaction acting on a specific molecule. This approach is only feasible if the structure of the transition state is sufficiently known, as was shown recently for chlorine isotope effects associated with dehalogenation of chlorinated alkanes by a haloalkane dehalogenase (106). A good agreement between calculated and experimental values was observed.…”
Section: Implications and Future Research Needsmentioning
confidence: 63%
“…47,116,169,217,220,[223][224][225][226][227][228][229] Bruice and co-workers have focused on identifying enzyme configurations that are most suitable for the nucleophilic attack. 116,227 However, Shurki et al suggested that these near attack conformations do not make important contributions to catalysis.…”
Section: Desolvation and Reactant State Effectsmentioning
confidence: 99%
“…[23][24][25][26] The activation barrier for the reaction between acetate and DCE was calculated to be about 23 kcal mol À1 in the gas phase. Solvent effects have a pronounced influence on the barrier for the reaction.…”
Section: Introductionmentioning
confidence: 99%